Simulated and experimental studies of a multi-band symmetric metamaterial absorber with polarization independence for radar applications. (1st April 2022) - Ali, Hema O.; Al-Hindawi, Asaad M.; Abdulkarim, Yadgar I.; Nugoolcharoenlap, Ekasit; Tippo, Tossapol; Alkurt, Fatih Özkan; Altintaș, Olcay; Karaaslan, Muharrem
Abstract : We develop a simple new design for a multi-band metamaterial absorber (MTMA) for radar applications. Computer Simulation Technology (CST) Studio Suite 2018 was used for the numerical analysis and absorption study. The simulated results show four high peaks at 5.6 GHz, 7.6 GHz, 10.98 GHz, and 11.29 GHz corresponding to absorption characteristics of 100%, 100%, 99%, and 99%, respectively. Furthermore, two different structures were designed and compared with the proposed MTMA. The proposed structure remained insensitive for any incident angle and polarization angle from 0° to 60°. Moreover, negative constitutive parameters were retrieved numerically. To support the simulated results, the proposed design was fabricated by using a computer numerical control-based printed circuit board prototyping machine and tested experimentally in a microwave laboratory. The absorption mechanism of the proposed MTMA is presented through the surface current and electric field distributions. The novelties of the proposed structure are a simple and new design, ease of fabrication, low cost, durability, suitability for real-time applications and long-term stability given the fabrication technique and non-destructive measurement method and very high absorption. The proposed structure has potential applications in C and X band frequency ranges.